A spy in the house of love: an introduction to Anais Nin A spy in the house of love: an introduction to Anais Nin - Ubiratan Paiva de Oliveira (Ilha do Desterro, 2008)
Anais Nin was born in Paris in 1903. Her father was a
Cuban pianist and composer and her mother a singer of French-Danish origin. At the age of nine, after her father had abandoned the family, she started writing her Diary, which consisted of over one hundred volumes at the time of her death in Los Angeles in 1977. When she was eleven, she was brought to New York where, at the age of sixteen, Nin started writing in English. Her first book to be published was D.H. Lawrence: An Unprofessional Study, in 1932. She also worked as a fashion and artist's model and as a Spanish dancer for some time Having been psychoanalysed by Otto Rank, she became his assistant. Anais Nin was born in Paris in 1903. Her father was a
Cuban pianist and composer and her mother a singer of French-Danish origin. At the age of nine, after her father had abandoned the family, she started writing her Diary, which consisted of over one hundred volumes at the time of her death in Los Angeles in 1977. When she was eleven, she was brought to New York where, at the age of sixteen, Nin started writing in English. Her first book to be published was D.H. Lawrence: An Unprofessional Study, in 1932. She also worked as a fashion and artist's model and as a Spanish dancer for some time Having been psychoanalysed by Otto Rank, she became his assistant.